The effect of service quality, utilisation of management information systems, and communication on participant satisfaction with trust as an intervening variable on Taspen pension participants in the Tanjungpinang City - Ningrum, Meisy Pujianti; Fachrudin, Fachrudin; Ngaliman, Ngaliman (Journal of Multidisciplinary Academic Business Studies, 2024)
Purpose: This study aimed to analyze the satisfaction of retired participants in Taspen in the Tanjungpinang city area. Methodology: This study adopted a quantitative approach using a sample of 150 retired participants. Data were collected through questionnaires and analyzed using SPSS version 23 and SEM-PLS version 4 to test the measurement and structural models. Results: Findings revealed that service quality and communication significantly affect trust, whereas the utilization of management information systems does not. In contrast, management information system utilization significantly affects satisfaction, whereas service quality and communication do not. Trust significantly affected satisfaction and mediated the relationship between service quality and satisfaction, but did not mediate the effects of system utilization and communication on satisfaction. The model explained 52.8% of the variance in trust and 48.9% of the variance in satisfaction. Conclusions: Participant satisfaction was strongly influenced by trust, which bridged service quality and satisfaction. However, the role of management information systems and communication in driving satisfaction is more direct than that of trust. Limitations: The study is limited to Taspen pension participants in Tanjungpinang City, which may reduce generalizability. Contribution: This study contributes empirical evidence to the pension service management literature by highlighting the mediating role of trust and offering practical insights for improving service delivery, system utilization, and communication strategies.